Effect of restricted suckling on the performance of sows (Indian Journal of Animal Production and Management, 2024)
Eighteen Hampshire sows with their litters were randomly selected and divided into three groups keeping  similar parities (1-4) from 4th week onwards viz. unrestricted suckling (T1), 6 hours restricted suckling  (T2) and 12 hours restricted suckling (T3) groups. All the animals were reared under standard feeding  and management conditions. The piglets were weaned at 8th week of age. The sows were observed  for reproductive performance in the successive lactation. The average body weight loss of sows during  4th to 8th week was found to be 16.13 ± 1.98, 11.42 ± 0.71 and 7.70 ± 0.73 kg in T1, T2 and T3 groups,  respectively, which differed significantly (P
Keywords: Hampshire Sows; Performanc; e Restricted suckling; Weight loss